Cold island : a novel - Colt, Peter, 1973- (Colt, Peter, 1973- Detective Tommy Kelly, 2025)
"Massachusetts State Police detective Tommy Kelly is called to Nantucket Island, where a boy's skeletal remains have been discovered at a construction site--interred for thirty-five years. The crime is especially gutting for Tommy, the father of two boys. It's also the beginning of a grim mystery. Because no child during that period was even reported missing. Tommy is partnered with Nantucket PD's best detective, Jo Harris, who first chafes at the idea of a mainlander encroaching on her territory. And their work together is only raising more troubling questions. Then a possible link is found to the decades-old case of a serial killer--a vigilantly hidden part of the past that this tight-knit community would prefer to forget and never speak of again. The secrets in their silence are so shocking they soon pull Tommy into a very dark place. Suddenly, offseason on Nantucket has never felt so cold, so isolating, or so dangerous."--